The role of effective teaching methods among faculty members from the point of view of students of the Faculty of Arts at Sebha University (Journal of Human Sciences, 2021)
The research aims to know: the extent to which the faculty members use effective teaching methods from the point of view of the students of the Faculty of Arts at Sebha University, and a questionnaire was applied to the effective teaching of faculty members questionnaire prepared by the two researchers. The questionnaire items included most of the skills used in the teaching methods studied in this research. It was distributed randomly, and the sample included students of the fifth, sixth, seventh and eighth semesters from the Department: Educational Planning and Administration, Psychology, Sociology, Media, English and French, and their number was (40) students. The sample at the Faculty of Arts at Sebha University have a point of view about the extent to which faculty members use effective teaching methods, and we find the most common effective teaching methods: the teaching method based on the use of the student’s ideas, which includes paragraphs (2, 6): (students are allowed to express their opinion during the presentation of the lecture, And it encourages students to think scientifically), and the method of teaching based on praise and criticism includes paragraphs (3, 10): (students are evaluated through their answers to questions related to the course, and the dialogue is provoked among students by asking questions during the lecture), and the existing teaching method On praise and criticism, it includes paragraph (14): (He uses the educational means available to him according to the educational situation), and the results showed that there were no statistically significant differences between the students’ responses about their opinion of the extent to which faculty members use the teaching methods in the college due to the variable (gender), and (Semester); While there are statistically significant differences between the students’ responses about their opinion of the extent to which the faculty members use the teaching methods in the college due to the variable (age), and there are also statistically significant differences between the students’ responses about their opinion of the extent to which the faculty members use the teaching methods in the college due to the variable (specialization).